The future of leadership : today's top leadership thinkers speak to tomorrow's leaders - Bennis, Warren G.; Spreitzer, Gretchen M.; Cummings, Thomas G. (Jossey-Bass business & management series., 2001)
A collection of wisdom and inspirational offerings, from todays business leaders to those who would be leaders tomorrow. Topics range from the arrival of the era of human capital to creating a context for creativity in the workplace. Examines challenging issues tomorrow's leaders may face.